2019
DOI: 10.1186/s12877-019-1178-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Singapore’s consumption of local fish, vegetables and fruits, meat and problematic alcohol use as risk factors of depression and subsyndromal depression in older adults

Abstract: Background Depression is a chronic mental disorder that severely impacts the older adult population globally. Nutritional psychiatry is an approach that has gained traction over the years. Exploring locally relevant consumption of common types of fish, vegetables and fruits (V&F), meat and problematic alcohol use (PAU) as risk factors associated with depression and subsyndromal depression (SSD) could reveal modifiable factors that could be targeted in the local older adult population in Singapore.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…Moreover, the indicated effect was studied and stated not only for fresh fruits and vegetables but also for fruit and vegetable products, such as juices [37,39,40,48,49,51,52,54,56,60,61,65,70,72,82,83,88,92,94], dried [37,49,54,66], and canned fruits and vegetables [37,38,49,50,58,65,66], salads [39,40,44,49,52,54,58,61,62,[72][73][74]89,93,94], soups [39,40,62], or ketchup [39,79], and even fo...…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the indicated effect was studied and stated not only for fresh fruits and vegetables but also for fruit and vegetable products, such as juices [37,39,40,48,49,51,52,54,56,60,61,65,70,72,82,83,88,92,94], dried [37,49,54,66], and canned fruits and vegetables [37,38,49,50,58,65,66], salads [39,40,44,49,52,54,58,61,62,[72][73][74]89,93,94], soups [39,40,62], or ketchup [39,79], and even fo...…”
Section: Discussionmentioning
confidence: 99%
“…), and 442 covered different topics. After title and abstract screening, a total of 73 articles were consulted in full, while at the end of the screening procedure, 17 articles were included in the systematic review [26,27,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Figure 1 shows the selection process.…”
Section: Literature Searchmentioning
confidence: 99%
“…Moreover, two studies reported separate data for men and women, and for this reason they were considered separately [26,55]. Furthermore, Barros et al reported separate data for minor and major depression [54], and Goh reported separate data for depression and subsyndromal depression, and for this reason they were considered separately [58]. Lastly, Won et al, reported data stratified by age groups (19-29; 30-49; 50-64 years), and for this reason, it was considered separately [67], resulting in 24 datasets being included in the meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…He doesn't leave the house even though I want to. "(1M) "Yes, I know that he doesn't want anybody to see him using a walking stick, that's why he stays at Risk factors for depression are complex and multifactorial [18].During aging, the change in the quality of life, and physical health problems and losses might cause loneliness to arise, and such feelings might threatenthe mental healthof elderly individuals.Decline in the trust towards other people, decline in financial support, anger, stress and fear of being exposed to violence might cause alienation and loneliness in an elderly individual [19].…”
Section: Resultsmentioning
confidence: 99%